Thursday

April 2, 2015

April 2, 2015

Posted by **babyc36** on Monday, August 19, 2013 at 7:26pm.

- math -
**Ms. Sue**, Monday, August 19, 2013 at 11:16pm6(x-1)=18x

6x - 6 = 18x

-6 = 12x

-6/12 = x

-1/2 = x

**Answer this Question**

**Related Questions**

math - when I have (2x^(3)-18x)-(2x^(3)) / (x^(2)-9) am I suppose to be left ...

Algebra - checking problem Use FOIL to multiply: (6x – 1)(3x – 4) 6x*3x + 6x*(-4...

Math - Find the Least Common multiple of the two expressions: 24x^2-96 & 18x^2+...

Math - How can we factor trinomial: 36x^2+18x+0 Is thislike this: 18x(2x+1)

Math - 9x^2+16y^2-18x+64y-71=0 find the coordinates of the center, the foci, and...

college algebra - y intercept: 3x^2+18x 0=3x^2+18x from here im lost

Math - i'm a bit stuck with this.. 145/18 = x + x^2 what does x equal to? ...

Pre-Cal - Classify the conic and write the equation in standard form: (1) 9x^2...

math - help my daughter has a math problem and came to me for help, I am lost...

math! - determine two geometreic sequences whose first terms are 18x-9, 2x+8 and...